In vitro Susceptibility Profiles and Clinical Distribution of Candida parapsilosis Species Complex Subtypes from Deep Infections to Nine Antifungal Drugs - Zhang, Wei; Zhan, Minghua; Wang, Na; Fan, Jingjing; Han, Xuying; Li, Caiqing; Liu, Jinlu; Li, Jia; Hou, Yongwang; Wang, Xinsheng; Zhang, Zhihua (Research Perspectives of Microbiology and Biotechnology Vol. 8, 2024)
Introduction: The Candida parapsilosis complex can be divided into C. parapsilosis sensu stricto, C. orthopsilosis, and C. metapsilosis subtypes. C. parapsilosis complex is the most predominant pathogen in the non-Candida albicans family. It is uncommon for drug sensitivity tests to type them. In routine susceptibility reports, drug susceptibility of C. parapsilosis complex subtypes is lacking. Aim: This study aims to investigate the antifungal susceptibility and clinical distribution characteristics of the C. parapsilosis complex subtypes causing deep infection in patients. Methodology: Non-repetitive strains of C. parapsilosis complex isolated from deep infection from 2017 to 2019 were collected. Blood culture, cerebrospinal fluid culture, and pus culture were enriched in a liquid medium. Species-level identification was performed using a matrix-assisted laser desorption/ionization time-of-flight mass spectrometer and confirmed using ITS gene sequencing, when necessary. Antifungal susceptibility testing was performed using the Sensititre YeastOne system method. Results: A total of 244 cases were included in the study, including 176 males (72.13%, 60.69±13.43 years) and 68 females (27.87%, 60.21±10.59 years). The primary diseases were cancer (43.44%), cardiovascular disease (25.00%), digestive system diseases, (18.44%), infection (6.97%), and nephropathy (6.15%). Strains were isolated from the bloodstream (63.11%), central venous catheters (15.16%), pus (6.56%), ascites (5.74%), sterile body fluid (5.33%), and bronchoalveolar lavage fluid (BALF, 4.09%). Of the 244 C. parapsilosis complex strains, 179 (73.26%) were identified as C. parapsilosis sensu stricto, 62 (25.41%) were C. orthopsilosis, and three (1.23%) were C. metapsilosis. Only one C. parapsilosis sensu stricto strain was resistant to anidu- lafungin, micafungin, caspofungin, and voriconazole, and it was non-wild-type (NWT) to amphotericin B. Furthermore, six C. parapsilosis sensu stricto strains were resistant to fluconazole, and one was dose-dependent susceptible. Five C. parapsilosis sensu stricto strains were NWT to posaconazole. Only one C. orthopsilosis strain was NWT for anidulafungin, micafungin, caspofungin, fluconazole, voriconazole, amphotericin B, and posaconazole, while the rest of the strains were wild-type. C. parapsilosis often leads to severe fungal infection in patients with low immune function, especially in children with low birth weight under 2 years old. In the present study, most of the infected population were cancer patients, accounting for nearly half of the samples, confirming that impaired immunity is a risk factor for C. parapsilosis sensu stricto infection. Conclusion: C. parapsilosis sensu stricto was the main clinical isolate from the C. parapsilosis complex in our hospital. Most strains were isolated from the bloodstream. The susceptibility rate to commonly used antifungal drugs was more than 96%. Furthermore, most of the infected patients were elderly male cancer patients. In summary, C. parapsilosis complex is a common clinical invasive infecting Candida pathogen that requires continuous attention to its epidemiological characteristics and mastering of its clinical threat evolution.